The Most Recent Discoveries in Heterocyclic Nanoformulations for Targeted Anticancer Therapy - Bhattacharya, Sankha; Patel, Rajat; Joshi, Aalind (Mini Reviews in Medicinal Chemistry, 2022)
Every day, new cases of cancer patients whose recovery is delayed by multidrug resistance and chemotherapy side effects are identified, which severely limit treatment options. One of the most recent advances in nanotechnology is the effective usage of nanotechnology as drug carriers for cancer therapy. As a consequence, heterocyclic nanocarriers were put into practice to see whether they could have a better cure with positive results. The potential of a therapeutic agent to meet its desired goal is vital to its success in treating any disease. Heterocyclic moieties are molecules that have a wide variety of chemically therapeutic functions as well as a significant biological activity profile. Heterocyclic nanoformulations play an important role in cell physiology and as possible arbitrators for typical biological reactions, making them valuable in cancer research. As a result, experts are working with heterocyclic nanoformulation to discover alternative approaches to treat cancer. Due to their unique physicochemical properties, heterocyclic compounds are real cornerstones in medicinal chemistry and promising compounds for the future drug delivery system. This review briefly explores the therapeutic relevance of heterocyclic compounds in cancer treatment, various nanoformulation, and actively describes heterocyclic magnetic nano catalysts and heterocyclic moiety, as well as their mode of action, which have favorable anti-cancer effects.
Keywords: nanoformulation